Fine-Tuning Florigen Increases Field Yield Through Improving Photosynthesis in Soybean - Xu, Kun; Zhang, Xiao-Mei; Chen, Haifeng; Zhang, Chanjuan; Zhu, Jinlong; Cheng, Zhiyuan; Huang, Penghui; Zhou, Xinan; Miao, Yuchen; Feng, Xianzhong; Fu, Yong-Fu (Frontiers in Plant Science, 2021)
Crop yield has been maintaining its attraction for researchers due to the demand of global population growth. Mutation of flowering activators, such as florigen, increases plant biomass at the expense of later flowering, which brings crops to failure of mature in field. As a result, it is difficult to apply flowering activators to agriculture production. Here, we developed a strategy to utilize florigen to significantly improve soybean yield in field. Through screening transgenic lines of RNAi-silencing florigen homologs in soybean (Glycine-max-Flowering Locus T Like, GmFTL), we identified a line GmFTL-RNAi#1, which displayed minor change in both GmFTL expression and flowering time, but notable increment of yield in soybean. Expectedly, GmFTL-RNAi#1 matured normally in field and exhibited markedly high yield over multiple locations and years. Results indicate that it is possible to reach the trade-off between flowering time and high yield through fine-tuning expression of flowering activators. Further studies uncovered a mechanism in which GmFTL negatively regulates photosynthesis, a substantial source for crop yield, demonstrating a novel function of florigen. Thus, due to highly conserved functions of florigen in plants and the classical RNAi approach, our findings provide a promising strategy harnessing early-flowering genes for improving crop yield.